A study of acetylcholinesterase and cholinesterase in the fetal mouse brain and a study of the effects of three teratogens, vitamin A, cyclophosphamide and sodium valproate on the fetal mouse central nervous system - Pillans, Peter Ian (Division of Clinical Pharmacology, 2018)
There were two aims in this thesis. Firstly, to investigate cholinesterase and its isoenzymes in the fetal mouse brain, and secondly to study drug-induced fetal damage with the following objectives in mind: (i) to examine new markers for the evaluation and prediction of the teratogenic potential of drugs, and (ii) to try and throw more light on pathogenic mechanisms of drug injury with particular reference to the developing fetal central nervous system. Acetylcholinesterase activity in brain homogenates was determined colorimetrically and the isoenzymes were separated by polyacrylamide gel electrophoresis. A cyanmethaemoglobin method was used to measure the contribution of acetylcholinesterase activity in blood to total brain esterase activity. Cholinesterase activity was estimated colorimetrically, and with the aid of enzyme inhibitors and polyacrylamide gel electrophoresis. The effects of three central nervous system teratogens, vitamin A, cyclophosphamide and sodium valproate when administered during embryonic development, on gross fetal parameters in C3H mice including embryolethality, gross morphological abnormalities, fetal weight, brain weight, brain acetylcholinesterase and its isoenzymes, and in some instances brain total protein content and choline acetyltransferase activity, were assessed. Preliminary studies were also performed with a view to future areas of research on (i) the effects of vitamin A when administered during the pre-implantation period on viability/esterase enzyme activity, cell number, mitotic index and chromosome structure in the 81h blastocyst; (ii) the influence of vitamin A on C3H fetal mouse brain proteins using high resolution two-dimensional electrophoresis; and (iii) the effects of cyclophosphamide and vitamin A on cephalic DNA damage utilising a DNA unwinding assay to detect DNA strand breaks. Substantial acetylcholinesterase activity of ± 3nmol/min/mg was present in 17-day to 19-day fetal mouse brains and 5 isoenzymes were present on electrophoresis. The contribution of acetylcholinesterase activity in blood was low at approximately 3%. Similarly, fetal mouse brain cholinesterase activity was found to be very low and the effect of teratogens on this enzyme was not assessed. A rise in the incidence of malformations and embryolethality with increase in dose, and after administration earlier in gestation occurred with all three teratogens. A growth-inhibitory effect was another feature although this was most pronounced after cyclophosphamide administration. Acetylcholinesterase activity was affected by the teratogen used and its time of administration as well as other factors such as growth inhibition, haemorrhage and repair processes. Vitamin A administration on day 10 of gestation was associated with a greater acetylcholinesterase activity compared with controls, which was not accompanied by a change in brain total protein content or choline acetyltransferase activity. Cyclophosphamide and sodium valproate administration during the embryonic period were associated with a lower acetylcholinesterase activity in near-term fetuses. However, in fetuses examined two days after cyclophosphamide administration there was a greater acetylcholinesterase activity associated with an increase in haemoglobin and a decrease in choline acetyltransferase. A higher acetylcholinesterase activity was also observed in exencephalic brains. Vitamin A administration was associated with a higher activity of isoenzyme 5 whereas cyclophosphamide and sodium valproate administration resulted in a lower peak height for band 4. When vitamin A was administered during the pre-implantation period 60h after copulation no effect on viability/esterase enzyme activity, cell number, mitotic index or chromosome structure was observed in 81h embryos. However, a striking incidence of abnormalities was noted in fetuses examined near term. This study suggested that teratogenic doses of vitamin A modified the brain protein pattern of the fetal mouse with a possible broad spectrum deletion of protein spots and the appearance of a limited number of new spots. There was no evidence of DNA strand breaks induced by vitamin A, which contrasted with obvious cephalic DNA damage after cyclophosphamide administration. The potential of these techniques in the prediction of the embryotoxicity of drugs, and progress in the understanding of underlying mechanisms are discussed.